Association between sociodemographic status and antiepileptic drug prescriptions in children with epilepsy - Mattsson, Peter; Tomson, Torbjörn; Edebol Eeg-Olofsson, Karin; Brännström, Lars; Ringbäck Weitoft, Gunilla (Epilepsia (Copenhagen), 2012)
Summary Purpose:  We investigated whether in Sweden sociodemographic differences are associated with access to expert health care and antiepileptic drug (AED) prescriptions in children with epilepsy. Methods:  Data on epilepsy, prescription of AEDs, and sociodemographic variables were obtained from several national administrative registers. We linked individual data to examine whether access by pediatric epilepsy patients to neuropediatricians and the prescription of individual AEDs differed according to gender, age, parental education, place of residence, parental region of birth, and household income. We also assessed whether AEDs are prescribed differently to patients with epilepsy by neuropediatricians as compared to other physicians. Key Findings:  Of 1,788,382 children aged 1–17 years in 2006, living in the country by the end of 2006, 9,935 had a diagnosis of epilepsy (0.56%). Patients with epilepsy on AED treatment (n = 3,631) comprised 0.24% of the total Swedish population aged 1–17 years. Out of 3631 patients with epilepsy on AED treatment, 2301 (63.4%) received prescriptions from a neuropediatrician. Children with epilepsy aged 1–5 years old—as opposed to older children and adolescents—and children with epilepsy residing in large cities—as opposed to children living in smaller cities and rural areas—were more likely to be treated by a neuropediatrician. Children living in large cities received oxcarbazepine to a greater extent than children living in rural areas. Levetiracetam was prescribed more extensively to children whose parents had higher incomes. Of the five most frequently used AEDs, three (lamotrigine, oxcarbazepine, and levetiracetam) were prescribed to a larger extent by a neuropediatrician rather than by other specialists, and one AED (carbamazepine) was prescribed to a lesser extent. Significance:  The results of this nationwide cross‐sectional study of children with epilepsy are important because they show that universal coverage for medical care does not eliminate inequalities of access to health care services among children and adolescents. No data are available that can guide us as to whether the density of child neurologists is of importance to access to expert health care, but this seems likely. Prescription patterns of AEDs differ between child neurologists and other specialists.